SARS-CoV-2 and Pregnancy: A Review of the Facts - Ricardo Mamber Czeresnia; Ayssa Teles Abrao Trad; Ingrid Schwach Werneck Britto; Romulo Negrini; Marcelo Luís Nomura; Pedro Pires; Fabricio da Silva Costa; Roseli Mieko Yamamoto Nomura; Rodrigo Ruano (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective The present comprehensive review aims to show the full extent of what is known to date and provide a more thorough view on the effects of SARS-CoV2 in pregnancy. Methods Between March 29 and May, 2020, the words COVID-19, SARS-CoV2, COVID- 19 and pregnancy, SARS-CoV2 and pregnancy, and SARS and pregnancy were searched in the PubMed and Google Scholar databases; the guidelines from well-known societies and institutions (Royal College of Obstetricians and Gynaecologists [RCOG], American College of Obstetricians and Gynecologists [ACOG], International Society of Ultrasound in Obstetrics & Gynecology [ISUOG], Centers for Disease Control and Prevention [CDC], International Federation of Gynecology and Obstetrics [FIGO]) were also included. Conclusion The COVID-19 outbreak resulted in a pandemic with > 3.3 million cases and 230 thousand deaths until May 2nd. It is caused by the SARS-CoV2 virus and may lead to severe pulmonary infection and multi-organ failure. Past experiences show that unique characteristics in pregnancy make pregnant women more susceptible to complications from viral infections. Yet, this has not been reported with this new virus. There are risk factors that seem to increase morbidity in pregnancy, such as obesity (body mass index [BMI] > 35), asthma and cardiovascular disease. Current reports describe an increased rate of pretermbirth and C-section. Vertical transmission